2013
DOI: 10.1038/ejcn.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward healthy eating: a mediator of the educational level–diet relationship

Abstract: BACKGROUNG/OBJECTIVES: A higher educational level is associated with a healthier diet. The goal of this study was to establish whether this association is mediated by attitudes toward healthy eating. SUBJECTS/METHODS: The cross-sectional MONA LISA-NUT study was performed in 2005-2007 on adults aged 35-64 years from northern and north-eastern France. Diet quality was assessed on the basis of a 3-day food record and a validated score based on French national dietary guidelines. Specific questions investigated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 36 publications
8
41
3
1
Order By: Relevance
“…Our result on the lack of relation of education with the nutritional status seems surprising since the level of education is commonly considered as a strong predictor of health behavior. Such result was confirmed by a French research including adults aged 35-64 -it showed that higher education related to the positive attitude towards healthy food and the choice of healthier products [16]. It was also revealed that children of the better-educated mothers consumed more portions of fruit and vegetables during the day and ate breakfasts more often that the children of lower-educated mothers did [39].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our result on the lack of relation of education with the nutritional status seems surprising since the level of education is commonly considered as a strong predictor of health behavior. Such result was confirmed by a French research including adults aged 35-64 -it showed that higher education related to the positive attitude towards healthy food and the choice of healthier products [16]. It was also revealed that children of the better-educated mothers consumed more portions of fruit and vegetables during the day and ate breakfasts more often that the children of lower-educated mothers did [39].…”
Section: Discussionsupporting
confidence: 72%
“…Social factors refer to the mother's socio-economic and socio-demographic features. Education, income or professional status indicate the socio-economic status (SES) of a particular person [15][16][17]. It is widely acknowledged that the higher the SES, the healthier the lifestyle, including diet [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Those Finnish adults who rated healthfulness over price and convenience consumed more fruit and vegetables and less energy-dense foods (Konttinen et al, 2012). Similar associations between nutrition-related attitudes, food purchasing behaviors (Turrell and Kavanagh, 2006; Gittelsohn et al, 2006), and other diet quality measures were observed in small-scale studies in France (Le et al, 2013), the UK (Traill et al, 2011), Australia (Turrell and Kavanagh, 2006), Finland (Konttinen et al, 2012), and the US (Gittelsohn et al, 2006; Pelletier et al, 2013; Aggarwal et al, 2014). …”
Section: Introductionsupporting
confidence: 70%
“…Food-related attitudes have been known to affect diet quality (Beydoun and Wang, 2008a, 2008b; Le et al, 2013; Acheampong and Haldeman, 2013; Traill et al, 2011; Turrell and Kavanagh, 2006; Gittelsohn et al, 2006). For example: In the US Continuing Survey of Food Intake by Individuals (CSFII 1994–96), perceived value of cost over nutrition was associated with lower quality diets and higher consumption of fats, added sugars and sodium, and vice a versa (Beydoun and Wang, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation